COMPREHENSIVE OVERVIEW ON RECENT UPDATES OF GASTRORETENTIVE RAFT-FORMING SYSTEMS - TEAIMA, MAHMOUD; ABDELMONEM, REHAB; SAADY, MARWA; EL-NABARAWI, MOHAMED; SHOMAN, NABIL A. (International Journal of Applied Pharmaceutics, 2022)
A Raft-forming system is an auspicious approach for systematic drug delivery with steady plasma profiles and drug sustained release manner. It has advantages like enhanced bioavailability, better floating capabilities than other floating systems, more patient compliance, and promoting drug efficacy. Although, it has some problems as it can’t be used for drugs that possess low acid solubility, drugs that are unstable in gastric media, and drugs used for selective release in the colon along with stability difficulties. This system can be successfully prepared by three methods: the physical approach, chemical approach, and physiologically-stimuli approach. The comparative studies showed that the raft-forming system has more advantage over the other comparatives in the antacid potency and in vitro gastric residence time, allowing an intact prolonged delivery of the antacid drug. All the listed applications of the raft system were, fortunately, possessing promising drug delivery with a well-designed drug delivery system. There was a good variety in the active ingredients formulated in a raft, starting from some anti-coughs, anti-spasmodic, anti-inflammatories, and antacids to drugs treating osteoporosis and finally anti-depressants and anti-epileptic drugs. This diversity along with simple in vitro and in vivo evaluations, gives the potentiality to raft for leading the other gastro retentive drug delivery systems for decades.